The effect of compression ratio on the performance, emissions and combustion of an SI (spark ignition) engine fueled with pure ethanol, methanol and unleaded gasoline - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
In this study, the effect of CR (compression ratio) on a SI (spark ignition) engine's characteristics of performance, combustion and emissions by using pure ethanol, methanol and unleaded gasoline were investigated experimentally. In the experiments, an SI engine having a CR of 8.5:1, having a single cylinder and air-cooled was used. These tests were conducted on four different CRs of 8.0:1, 8.5:1,9.0:1 and 9.5:1 with a wide-open throttle, original ignition timing and at 2400 rpm. The test results obtained from the three fuel types were compared to each other. The results were shown that the BMEP (brake mean effective pressure), CGP (cylinder gas pressure), BTE (brake thermal efficiency), and BSFC (brake specific fuel consumption) obtained with the use of ethanol and methanol at all CRs were generally increased when they were compared to those of pure gasoline. In general, pure ethanol and methanol provided a lower exhaust emission compared to gasoline's emissions at all CRs. Furthermore, with an increasing CR, the CGP generally increased with the usage of pure ethanol and methanol as compared to unleaded gasoline's study and the CGP and HRR(heat release rate) rose earlier than those values in unleaded gasoline. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Ethanol; Methanol; Exhaust emissions; Combustion characteristics; Engine performance; Compression ratio; EXHAUST EMISSIONS; ALCOHOL FUELS; BLENDS; REDUCTION; HYDROGEN